W and Z boson production in p-Pb collisions at √sNN=5.02 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (Journal of high energy physics, 2017)
The W and Z boson production was measured via the muonic decay channel in proton-lead collisions at sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV at the Large Hadron Collider with the ALICE detector. The measurement covers backward (−4.46 < y cms < −2.96) and forward (2.03 < y cms < 3.53) rapidity regions, corresponding to Pb-going and p-going directions, respectively. The Z-boson production cross section, with dimuon invariant mass of 60 < m μμ < 120 GeV/c 2 and muon transverse momentum (p T μ ) larger than 20 GeV/c, is measured. The production cross section and charge asymmetry of muons from W-boson decays with p T μ > 10 GeV/c are determined. The results are compared to theoretical calculations both with and without including the nuclear modification of the parton distribution functions. The W-boson production is also studied as a function of the collision centrality: the cross section of muons from W-boson decays is found to scale with the average number of binary nucleon-nucleon collisions within uncertainties. Open image in new window
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F. Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere]
Gesehen am 17.10.2018